DETERMINAN TINGKAT PARTISIPASI ANGKATAN KERJA PEREMPUAN: STUDI KASUS INDONESIA 2010-2024: (DETERMINANTS OF FEMALE LABOR FORCE PARTICIPATION: A CASE STUDY OF INDONESIA 2010-2024) - Fitrania, Sernanda; Rochaida, Eny (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
The purpose of this study is to determine and analyze the influence of education level, women's productive age and GRDP on the level of female labor force participation in Indonesia. This study uses secondary data with multiple linear regression SPSS 2.5 version software. The conclusions of the research results are as follows: 1) Education level has a positive and significant effect on the level of female labor force participation in Indonesia 2) women's productive age has a negative and significant effect on the level of female labor force participation in Indonesia 3) GRDP has a positive and significant effect on the level of female labor force participation in Indonesia.